PERUBAHAN PENGETAHUAN, SIKAP, DAN PRAKTIK JAJANAN ANAK SEKOLAH DASAR PESERTA PROGRAM EDUKASI PANGAN JAJANAN - Briawan, Dodik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The study objective was to analyze the effect of nutrition education programs on snacking behavior of school children. A pre-post intervention study was conducted at 13 districts/cities from 8 provinces in Indonesia, and involved 1,600 grade 5 school children. The snack education program was done by PT Unilever Indonesia in the period of May 2016. The intervention was conducted at the schools by applying education media such as flipcharts, posters and audio-kinetic for children exercices. A self-administered measurement by a validated questionnaire was applied to assess knowledge, attitudes and practices before and after the program. The results showed that before intervention there are 50.9% of school children had good knowledge, 82.8% had good attitude, 34.0% of children had bad practices on snacks food. After the education program, the good knowledge increase by 16.2% and the good attitudes increased by 7.4% of children. Only few students (2.7%) increased practices on good snacking, meanwhile there was 13.4% decrease on poor snack practices. In conclusion, the education program could improve the snacking behavior in school children.Keywords: attitudes, knowledge, practices, school children, snack food